Pluses and minuses of ammonium and nitrate uptake and assimilation by phytoplankton and implications for productivity and community composition, with emphasis on nitrogen‐enriched conditions. (11th October 2015) - Glibert, Patricia M.; Wilkerson, Frances P.; Dugdale, Richard C.; Raven, John A.; Dupont, Christopher L.; Leavitt, Peter R.; Parker, Alexander E.; Burkholder, JoAnn M.; Kana, Todd M.
Abstract: Anthropogenic activities are altering total nutrient loads to many estuaries and freshwaters, resulting in high loads not only of total nitrogen (N), but in some cases, of chemically reduced forms, notably NH 4 + . Long thought to be the preferred form of N for phytoplankton uptake, NH 4 + may actually suppress overall growth when concentrations are sufficiently high. NH 4 + has been well known to be inhibitory or repressive for NO 3 ‐ uptake and assimilation, but the concentrations of NH 4 + that promote vs. repress NO 3 ‐ uptake, assimilation, and growth in different phytoplankton groups and under different growth conditions are not well understood. Here, we review N metabolism first in a "generic" eukaryotic cell, and the contrasting metabolic pathways and regulation of NH 4 + and NO 3 − when these substrates are provided individually under equivalent growth conditions. Then the metabolic interactions of these substrates are described when both are provided together, emphasizing the cellular challenge of balancing nutrient acquisition with photosynthetic energy balance in dynamic environments. Conditions under which dissipatory pathways such as dissimilatory NO 3 − / NO 2 − reduction to NH 4 + and photorespiration that may lead to growth suppression are highlighted. While more is known about diatoms, taxon‐specific differences in NH 4 + and NO 3 − metabolism that may contribute to changes in phytoplankton community composition when the composition of the N pool changes are presented. These relationships have important implications for harmful algal blooms, development of nutrient criteria for management, and modeling of nutrient uptake by phytoplankton, particularly in conditions where eutrophication is increasing and the redox state of N loads is changing.